The Ladder of Power in Nasseerian Iran. - Ismael, Fatima Saloom (International Humanities Studies, 2020)
This article studies the structure of power in the Nasserian era in Iran through exploring two categories as one framework of power structure and the nature of domination and authority. The characteristic of the structure of power in Iran during the Nasserian era was dictatorship. The king was the center of gravity and the distribution of power. In this structure, the government, the court, and the king were indivisible. Consequently, they constituted obstacles to the formation of legitimate institutions and to the emergence of a bureaucratic and political structure outside the purview of the autocratic system. Existing was not possible. In such a structure, developing social classes outside the control of the government was not possible. The introduction of new ideas and the first attempts to reform Iran took place in the Qajar era and were faced with challenges in the power structure. On the other hand, with the rapid growth of foreign trade and the increasing collision of Iranian businessmen with the west, the foreign trips and acquaintance with the achievements of western civilization, they became aware of their class status and their class interests against the Qajar government.